How to identify sugar-cane diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Koike Hideo, 1988. 'Sugar-Cane Diseases: a guide for field identification', 127pp. ISBN 92 5102534 7, FAO, Rome